Manligt; det nya kvinnliga. En problematisering av könsstereotyp makt och preferens - Olsson Mäkinen,Jesper; Wilhelmsson,Herta Matilda Linnéa (2022)
The aim of the study was to investigate the Preferene Weighted Power between different nationalities and genders. Power is a complex concept, and the definitions differ between contexts. To eliminate these contexts’ impact on the perception of power, the term Preference Weighted Power (PWP) has been used in an earlier experiment by Sikström et al. (2020). PWP weights the importance of a power domain against the perceived power in that domain, to eliminate the power’s context. We gathered survey responses from 591 participants to distinguish whether there is a gender difference in preference of power or not, and what gender is more powerful regarding public and private power, if we eliminate that context. We also conducted the study in three different countries, Greece, Sweden, and the United States, to see whether there was any difference in preference of power between them. The last purpose was to replicate Sikström et al. (2020) study to see whether PWP works in a smaller form. We found that women in fact have more private and public power, and more power once measured with PWP. We found cultural differences in the perception of power, where the Greek participants valued public power higher than both Americans and Swedes. The smaller form of PWP was adequately replicated. There are similarities between the scales, but it needs to be researched more thorough in future studies.
Keywords: makt; kön; Preferense Weighted Power; tvärkulturell; könsskillnader; power; gender; Preference Weighted Power; cross-cultural; gender differences